The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1002/anie.201609477
|View full text |Cite
|
Sign up to set email alerts
|

Magnetically Induced Continuous CO2 Hydrogenation Using Composite Iron Carbide Nanoparticles of Exceptionally High Heating Power

Abstract: The use of magnetic nanoparticles to convert electromagnetic energy into heat is known to be a key strategy for numerous biomedical applications but is also an approach of growing interest in the field of catalysis. The heating efficiency of magnetic nanoparticles is limited by the poor magnetic properties of most of them. Here we show that the new generation of iron carbide nanoparticles of controlled size and with over 80 % crystalline Fe C leads to exceptional heating properties, which are much better than … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
167
0
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 138 publications
(177 citation statements)
references
References 31 publications
7
167
0
3
Order By: Relevance
“…Transition metals (e. g., Fe, Mn, Ni) were previously reported to possess high selectivity for producing CO as electrocatalysts of CO 2 RR . Recent researches have shown that the Fe/Fe 3 C is a promising precious metal free catalyst for a series of important reactions, including CO 2 hydrogenation catalysts, and ammonia decomposition processes, inspiring us to study the electrocatalytic properties of Fe/Fe 3 C toward CO 2 RR.…”
Section: Introductionmentioning
confidence: 99%
“…Transition metals (e. g., Fe, Mn, Ni) were previously reported to possess high selectivity for producing CO as electrocatalysts of CO 2 RR . Recent researches have shown that the Fe/Fe 3 C is a promising precious metal free catalyst for a series of important reactions, including CO 2 hydrogenation catalysts, and ammonia decomposition processes, inspiring us to study the electrocatalytic properties of Fe/Fe 3 C toward CO 2 RR.…”
Section: Introductionmentioning
confidence: 99%
“…The spatial separation of the heating agent and the catalyst, by depositing Fe 2.2 C NPs on an inorganic support previously impregnated Ru or Ni NPs, led to CH 4 yields higher than 90 % at low magnetic field (ca. 20 mT) . Almost simultaneously, Mortensen et al .…”
Section: Figurementioning
confidence: 94%
“…Magnetic induction has recently appeared as an alternative heating source for heterogeneous catalytic reactions . It consists in applying high‐frequency alternating magnetic fields to ferromagnetic materials to release heat through hysteresis losses.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…Magnetic nanoparticles (NPs) are objects of choice for a wide range of applications, such as data storage,, catalysis, and biomedical ones ,. Among the different properties sought, the potential overheating of the nanoparticles in presence of an alternate magnetic field received tremendous interest due to its implication on Magnetic Field Hyperthermia (MFH) treatment and thermally‐assisted catalysis ,. To benefit from optimized heating properties, high saturation magnetization (M S ) materials are mandatory ,.…”
Section: Introductionmentioning
confidence: 99%